WORK AND INTERSUBJECTIVITY FROM THE SPEECHES AND EXPERIENCES OF THE MASONS WHO BUILD METROPOLITAN LIMA - REYES-ALVARADO, Felipe (2024)
The article seeks to understand and analyze what the construction trade entails in labor segments. In which the following components stand out: the migration, the informal and the self-construction, as social reproducers of the urban structure. This occurs according to 8 masons who carry out this activity in Metropolitan Lima. Therefore, the volume of information rescued and reflected in this writing is the result of the methodological tactic of “insertion into the field”, that is, where the researcher resorts to the role of construction assistant between the months of December 2023 and February 2024. By accompanying and monitoring the work with the bricklayers,semi-structured interviews, unplanned conversations and a record inside the construction site were collected. In the findings, it is a preliminary ethnographic approach that represents for the actors of this study: a work practice that arises in self-constructive and informal spaces, constructive knowledge acquires meaning and is born in the community, and the circularity of the construction work in the urban space.